Esquistossomose Mansônica no Estado de São Paulo: Aspectos Epidemiológicos - de Souza, Doralice; de Carvalho Ciaravolo, Ricardo Mario; Yohko Kanamura, Hermínia; Gargioni, Cybele; MacDowell Gonçalves Falcão, Ana Cecília; de Paula Eduardo, Maria Bernadete (BEPA. Boletim Epidemiológico Paulista, 2005)
ver pdf